Commodity Branding A Qualitative Research Approach to Understanding Modern Energy Brands - Larsen, Fridrik (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
When it comes to branding the energy space, an exciting and largely unexplored field of research emerges. Energy companies are under the spotlight as consumers press for positive action on sustainability, CSR, and environmental issues. In light of this, this book has two objectives. First, the author explores the challenges and opportunities that experts within the field face when deciding on strategic brand direction. The results indicate that practitioners in recently liberalised markets have met the emerging branding challenges, such as differentiating commodities, meeting new consumer demands, and building strong brands. Second, the book examines, from an expert-practitioner point of view, whether branding and building brands are activities relevant to this type of market. This book, therefore, attempts to fill a literature gap, as it examines the applicability of theoretical and practical methods of branding and brand strategies in a commodity market, in this case the energy market. Fridrik Larsen is an Associate Professor of marketing at the University of Iceland. He is a leading authority on branding within the energy space and the first individual to hold a PhD in energy branding. Larsen holds graduate degrees in finance, economics and psychology, and a postgraduate degree in marketing. He is the author of three books on energy branding, including Energy Branding (Palgrave Macmillan, 2017) and is a sought after public speaker and the founder of the international CHARGE conference.
1.Introduction -- 2.Literature review on energy branding and related fields. 3.Methodology: A qualitative approach -- 4.Findings: Understanding modern energy brands -- 5. Conclusion: Conceptual model of branding in the energy markets -- 6.References.
Keywords: Branding (Marketing).; Branding